การประเมินเบื้องต้นการปนเปื้อนโคลิฟอร์มแบคทีเรีย ของส้วมสาธารณะในเขตเทศบาลนครเชียงใหม่ - กล่อมเกษม แสงจันทร์ (Community and Social Development Journal, 2014)
การวิจัยนี้เป็นการประเมินเบื้องต้นการปนเปีอนเชื้อโคลิฟอร์มแบคทีเรียของส้วมสาธารณะในเขตเทศบาลนครเชียงใหม่ 84 แห่ง เก็บตัวอย่างการปนเปีอนอุจจาระภายในห้องส้วม 13 จุด จำนวน 922 ตัวอย่าง โดยใช้แบบประเมินมาตรฐานส้วมสาธารณะระดับประเทศ (HAS) และชุดทดสอบโคลิฟอร์มแบคทีเรีย (SI-2) ระหว่างเดือนมีนาคม-พฤษภาคม 2554วิเคราะห์ข้อมลโดยใช้สถิติพรรณนาเพื่อหาค่าร้อยละ ผลการศึกษามาตรฐานส้วมสาธารณะพบว่า ผ่านเกณฑ์ HAS เพียง 4 แห่ง (ร้อยละ 4.8) คือสถานีขนส่งทางบก สถานีบริการนํ้ามันเชื้อเพลิง สถานที่ราชการและศาสนสถานในเกณฑ์ความสะอาด (Healthy : H) อันดับแรกคือ สภาพท่อระบายสิ่งปฏิกูลและถังเก็บกักนํ้าไม่รั่วแตกหรือชำรุด ร้อยละ 90.5 ปัญหาที่พบมากคือ ไม่จัดให้มีการทำความสะอาดและระบบการควบคุมตรวจตราเป็นประจำ ร้อยละ 48.8 เกณฑ์ความเพียงพอ (Accessibility : A) มีส้วมพร้อมใช้งานตลอดเวลาที่เปีดให้บริการ ร้อยละ 97.6 พบว่าไม’มีส้วมนั่งราบสำหรับผู้พการ ผู้,สูงวัย หญิงตั้งครรภ์ ร้อยละ 86.9 เกณฑ์ความปลอดภัย (Safety : S) ส้วมสาธารณะไม่อยู่ที่ลับตา/เปลี่ยว ร้อยละ 100 ส่วนข้ออื่นๆ ผ่านเกณฑ์ไต้มากกว่าร้อยละ 78.6 ขึ้นไป ผลการศึกษาการปนเปีอนเชื้อโคลิฟอร์มแบคทีเรีย พบมากที่สูดในส้วมสาธารณะของสวนสาธารณะ, ตลาดสด และโรงเรียนร้อยละ 36.4, 34.6 และ 33.3 ตามลำดับ ส่วนห้องส้วมในห้องอาหารโรงแรม พบการปนเปี้อนน้อยที่สุด ร้อยละ 1.4 และพบการปนเปีอนในห้องส้วมชายมากกว่าส้วมหญิง(ร้อยละ18.9 และ 18.4) Preliminary Assessment on Coliform Bacteria Contamination of Public Toilets in Chiangmai Municipality This study was pre assessment on coliform bacteria contamination of public toilets in Chiang Mai Municipality. Samples sizes were 84 public toilets and 922 samplings of 13 points that’s exposed to fecal contamination during March-May 2554. Methods used national standard pattern of public toilets (HAS) and coliform bacteria test (SI-2). Data analysis by descriptive statistics and percentage. The results showed that 4 public toilets were in standard of public toilets (HAS) on 4.8%. The first of healthy (H) requirements were tanks and drainage sewages were in good conditions (90.5%). A problem was the provision of cleaning and regular monitoring system control (48.8%). The accessibility (A) requirements were found available in public toilets 97.6% while 86.9% hadn’t been provided seat flat toilet for disabled, elderly and pregnancy. The safety (S) requirements, 100% of public toilets location were in sight/desolated and the others requirements could pass evaluation more than 78.6%. The study on coliform bacteria contamination was shown the percentage of contaminated conditions of the public park toilets, markets and municipal schools were 36.4, 34.6 and 33.3% respectively. The hotel’s restaurants showed least contamination (1.4%) and also found that men toilets contamination were more than women (18.9%, 18.4%).